ORGANIZE AN INTEGRATED DEVELOPMENT OF UNDERGROUND SPACE OF MEGAPOLISES - Pustovoytenko, V. P.; Havrish, O. R. (Science and Transport Progress, 2010)
The problem of forecasting the trends of urbanization, the main factors influencing the modern methods of organization of development of the underground construction of mega-cities, during the substantiation of field of integrated use and composition of organizational-and-technological schemes of development of underground space, is considered.